Historical context in the preservation of Khabarovsk architecture - Smolianinova, Tatiana (project baikal, 2025)
The article examines the history of the formation of the architecture of Khabarovsk, one of the key historical cities of the Far East. It presents the periodization of the development of the city’s architecture in the context of economic and political processes. The article notes the features of historical development and modern problems associated with its preservation and integration into the urban landscape. It also emphasizes the importance of an integrated approach that covers both architectural and historical aspects. This approach allows us to develop effective strategies for preserving and modernizing historical zones.
Keywords: Khabarovsk; architecture; cultural heritage site; public space; integration; urban environment